The Diffusion of Religion among Young Students of the University of Bari - Mongelli, Angela; Contini, Paolo; Rubino, Raffaella; Gentile, Fabrizio (Richtmann Publishing, 2020)
Religion has always been an extraordinary element of social cohesion, despite the fact that over the centuries its structure and power of influence adjusted to the epochal changes that, especially during the 20th century, have affected societies in the world. Through research, we wanted to highlight the features that characterise the concept of religiosity among young university students, with a focus on the intensity of religious sentiment, the relationship with God and, contextually, the religious institution, attested by attendance to the rites. This research, that was carried out through a structured questionnaire with closed answers, involved a population consisting of students enrolled in master or postgraduate courses and others enrolled in the fourth and fifth year of single-cycle courses of the University of Bari Aldo Moro in the academic year 2017-2018. The results show that, despite the large part of the sample declares itself a Christian Catholic faith, only a small part constantly attends religious services; rather, the percentage of students declaring to pray often or daily is quite relevant. We are witnessing a change in the way young people enjoy religion: more individual, more emotional, syncretically directed to the individual, rather than to a uniformly defined category.